The Effect of Employee Engagement and Quality of Work Life on Employee Performance with Organizational Citizenship Behavior as an Intervening Variable - Devi Kurniawati; Muryati; Survival (Journal of Management Research and Studies, 2024)
This study aims to obtain empirical evidence of the effect of employee engagement and quality of work life on employee performance with organizational citizenship behavior as an intervening variable. The population in this study were all employees at the Probolinggo Regional Inspectorate, totaling 122 employees. The determination of the number of samples using the slovin formula, which is 94 people. The data analysis technique used in this study is Partial Least Square-Structural Equation Modeling (PLS-SEM) using smartPLS software version 4.0. The results of the study show that although employee engagement is getting stronger, it is not able to encourage increased employee performance. Better employee engagement is able to encourage increased organizational citizenship behavior. Better quality of work life is able to encourage increased employee performance. Better quality of work life is able to encourage increased organizational citizenship behavior. Higher organizational citizenship behavior is able to encourage increased employee performance. Organizational citizenship behavior plays a role in fully mediating the influence of employee engagement on employee performance. Organizational citizenship behavior plays a role in partially mediating the influence of quality of work life on employee performance.